PENGEMBANGAN MEDIA PEMBELAJARAN BOOKLET BERBASIS REPRESENTASI PADA TOPIK DUALISME GELOMBANG PARTIKEL - Andi Yosua Pakiding; Marianus Marianus; Jeane Verra Tumangkeng (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to develop a representation-based booklet learning media on the topic of particle wave dualism. The development of learning media is a series of processes or activities to produce a learning media based on development theory. This research was carried out at the Physics Department, Manado State University, for students in the fifth semester of the 2022/2023 academic year. The type of research used is research on the development of R&D (Research and Development) 4D model (define, design, development, and dissemination). The instruments used to collect research data are validation sheets and questionnaires. To analyze the research data used descriptive percentage analysis technique. Material experts give an assessment of the booklet by 85% and media experts by 98.52% with valid or appropriate criteria. Students in the small group trial gave a positive assessment response to the indicators asked by 100% and in the large group trial it was 98.09%. The results showed that the booklet developed was suitable for use as a medium for learning physics among students.